The Community Relations Strategy Through the 9th NextDev Program as the Implementation of Corporate Social Responsibility by PT Telekomunikasi Selular (Telkomsel) - Dhea Andita Sari Saroso; Mochammad Kresna Noer (Universitas Multimedia Nusantara, 2024)
The growth of digital startups in Indonesia faces major challenges, including limited access to funding, low digital literacy, and uneven infrastructure, which hinder business sustainability. PT Telekomunikasi Selular (Telkomsel), through its CSR program